The 677C→T variant of MTHFR is the major genetic modifier of biomarkers of folate status in a young, healthy Irish population. Issue 6 (19th October 2018) - Shane, Barry; Pangilinan, Faith; Mills, James L; Fan, Ruzong; Gong, Tingting; Cropp, Cheryl D; Kim, Yoonhee; Ueland, Per M; Bailey-Wilson, Joan E; Wilson, Alexander F; Brody, Lawrence C; Molloy, Anne M
ABSTRACT: Background: Genetic polymorphisms can explain some of the population- and individual-based variations in nutritional status biomarkers. Objective: We sought to screen the entire human genome for common genetic polymorphisms that influence folate-status biomarkers in healthy individuals. Design: We carried out candidate gene analyses and genome-wide association scans in 2232 young, healthy Irish subjects to evaluate which common genetic polymorphisms influence red blood cell folate, serum folate, and plasma total homocysteine. Results: The 5, 10-methylenetetrahydrofolate reductase ( MTHFR ) 677C→T (rs1801133) variant was the major genetic modifier of all 3 folate-related biomarkers in this Irish population and reached genome-wide significance for red blood cell folate ( P = 1.37 × 10 −17 ), serum folate ( P = 2.82 × 10 −11 ), and plasma total homocysteine ( P = 1.26 × 10 −19 ) concentrations. A second polymorphism in the MTHFR gene (rs3753584, P = 1.09 × 10 −11 ) was the only additional MTHFR variant to exhibit any significant independent effect on red blood cell folate. Other MTHFR variants, including the 1298A→C variant (rs1801131), appeared to reach genome-wide significance, but these variants shared linkage disequilibrium with MTHFR 677C→T and were not significant when analyzed in MTHFR 677CC homozygotes. No additional non- MTHFR modifiers of red blood cell or plasma folate were detected. Two additional genome-wide significant modifiers of plasma homocysteine were found in the region of the dipeptidase 1 (DPEP1 ) gene on chromosome 16 and the Twist neighbor B ( TWISTNB ) gene on chromosome 7. Conclusions: The MTHFR 677C→T variant is the predominant genetic modifier of folate status biomarkers in this healthy Irish population. It is not necessary to determine MTHFR 677C→T genotype to evaluate folate status because its effect is reflected in concentrations of standard folate biomarkers. The MTHFR 1298A→C variant had no independent effect on folate status biomarkers. To our knowledge, this is the first genome-wide association study report on red blood cell folate and the first report of an association between homocysteine and TWISTNB .